Professional values and job satisfaction neonatal intensive care unit nurses and influencing factors: A descriptive correlational study - Zahra Eskandari Kootahi; Negar Yazdani; Hamidreza Parsa; Atila Erami; Reza Bahrami (Elsevier, 2023)
Background: Since the neonatal intensive care unit (NICU) is a vital ward in the hospital, evaluating NICU nurses' satisfaction and professional values is vital for improving health care quality. This study aimed to investigate professional values and nurses' job satisfaction in NICU nurses and influencing factors. Methods: This analytical cross-sectional study was conducted on 316 NICU nurses in NICUs of nine hospitals in Fars province, Iran, from October 2018 to May 2019. The subjects were selected by the census method. Herzberg's Job Satisfaction Questionnaire and Nurses Professional Values Scale-Revised were used for data collection. Data were analyzed by SPSS version-24. Results: Results showed a significant correlation between the total score of professional values and job satisfaction and also with its subscales (i.e., motivational and hygiene factors) (P < 0.001). However, age, marital status, education level, and working position were predictors of professional values, and type of hospital, insurance, and income were predictors of job satisfaction (P < 0.001). In motivational factors, job satisfaction was related to nursing values such as trust, caring, activism, professionalism, and justice (P < 0.001). Conclusion: Generally, job satisfaction was significantly correlated with nursing professional values in all subscales, especially trust. Furthermore, being single and working in a private hospital was associated with higher professional values and job satisfaction. Therefore, managers should provide better facilities and work conditions for their personnel. In addition, they are recommended to create a sense of trust between nurses and their coworkers.